Characteristics of Qur’anic Manuscripts in Southeast Asia: A Study of Codicological and Philological Literature in West Kalimantan - Ramadhan, Ahmad Fadhail; Jabbar, Luqman Abdul; Khalil, Muhammad Amin (Peneliti.net, 2026)
This study aims to identify and analyze the characteristics of Qur'anic manuscripts in West Kalimantan through a literature study approach. The existence of Qur'anic manuscripts in this region not only represents the transmission of the sacred text but also reflects the social, cultural, and intellectual dynamics of local Muslim communities during the spread of Islam in the archipelago. The study employed qualitative methods with content analysis techniques, analyzing various academic sources, such as journal articles and research reports relevant to the study of Qur'anic manuscripts and manuscripts in West Kalimantan. The results indicate that the study of Qur'anic manuscripts in West Kalimantan is still dominated by codicology and physical descriptions, with a focus on material aspects, types of rasm, khat, illumination, and the context of palace patronage. Manuscripts found in areas such as Sambas, Sintang, Landak, and Pontianak exhibit diverse material characteristics, including the use of local materials such as tapa bark and imported European paper, indicating the existence of global trade networks. In terms of layout, the main text is generally written in black ink with red ink as markers for syakl and waqf, accompanied by skolia such as maqra and juz, which indicate the manuscript's pedagogical function in religious education. These findings confirm that the Qur'an manuscripts in West Kalimantan are the result of the interaction between local traditions and the broader Islamic scholarly network in the archipelago. Therefore, further comparative and interdisciplinary research is needed to uncover textual variants, scholarly transmission networks, and the position of West Kalimantan manuscripts within the tradition of copying mushafs in the Southeast Asian region.